Assessment of the language, communication and interaction competences and skills of a patient with aphasia following aneurysm clipping and diagnosed symptomatic epilepsy - Gliwa, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The article describes a case of a patient with aphasia, diagnosed with symptomatic epilepsy seizures after aneurysm clipping. A speech therapy diagnosis was made, consisting of patient observation, analysis of clinical documentation and speech test results. The subject was diagnosed with disorders of linguistic competence and skills caused by the presence of acoustic-mnestic aphasia. Their consequences are dysfunctions in terms of communication and interaction skills and abilities.